EVALUASI KUALITAS ASET ALUN-ALUN KAWALI KABUPATEN CIAMIS - Nurlaila Fadjarwati; Handika Adimasputra Senjaya (KURVATEK, 2023)
Alun-Alun Kawali is an asset belonging to the Ciamis Regency which is managed by Dinas Perumahan Rakyat Kawasan Permukiman dan Lingkungan Hidup which is located in the Kawali sub-district. Based on the results of a preliminary survey conducted in the field, indications of problems related to asset quality are found, including lighting, seating areas and parking lots. Therefore an asset quality evaluation is carried out using five dimensions, namely Architectural, Aesthetic, Social, Environmental, and Functional. The research method used is descriptive research. Data collection techniques used are observation and interviews. The results of the assessment in general show that there are several problems with 10 indicators out of a total of 16 indicators regarding the availability and condition of Kawali Square assets which are still not in accordance with the standards.